The importance of the services sector in the State of Paraná - Kureski, Ricardo (2012)
The purpose of this study is to trace the recent development of the service sector in the economy of Paraná and analyze its participation in Paraná’s Gross Domestic Product, the evolution in occupation and the rate of formalization in the state. The reason of this study is the growth of the service sector importance in generating income and employment. The results reveal the increasing of the service participation in the added value from 60,3% in 2002 to 60,08% in 2007. In terms of occupation, this sector incremented 18,13% between 2002 and 2009. Finally, the results demonstrate the informal employment reduction, mainly due to the considerable decreasing of this type of worker in the market.